Quality of life of contraceptive users at urban community pharmacy / Wan Mohd Hamidi Wan Sulaiman - Wan Sulaiman, Wan Mohd Hamidi (2014)
Introduction: Contraception provides many benefits to married couples or couples on a consensual relationship. This study expects to evaluate quality of life among contraceptive users at community pharmacy settings and in addition to that will provide evidence to community pharmacists to improve their pharmaceutical care in the context of sexual and reproductive health among its customers. Method: A cross-sectional study was conducted by administering the WHOQOL BREF questionnaires to customers who obtain condom or contraceptive pills at urban community pharmacies in Kuala Lumpur and Selangor. Socio-demographic questionnaires were also administered to the respondents. Respondents' QOL score and socio-demographic characteristics were further analysed and interpreted with appropriate statistical tests. Results: All of 375 respondents reported high quality of life scores in all domains. The mean score for each item were in the range from 3.33 to 3.96. The top three most positive QOL items were: self-esteem (mean = 3.96, SD = 0.68), spirituality/religion/personal beliefs (mean = 3.94, SD = 0.71), and personal relationships (mean = 3.87, SD = 0.82). The QOL score among domain were highest in the social domain (mean = 15.37, SD = 2.71) and the lowest score were in the physical domain (mean = 13.56, SD = 1.81). Conclusions: Overall quality of life scores were high in both contraceptive groups and the highest score were reported in the social domain and the lowest in the physical domain.